The Effect of Obesity and Flexibility Toward Women’s Body Fat in Productive Age at Larasati Gymnastic Semarang Member - Eva Faridah (UNIB Press, 2021)
Obesity is an body fat increase. Overweight is a relative body weight increase when compared to the standard. Overweight then became a term that represented